Patterns of Teacher Pedagogical Creativity in Cultural Arts and Crafts Subjects in Elementary Schools - Wijayanti, Okto; Irawan, Dedy; Muryaningsih, Sri; Fah, Lay Yoon (Universitas Muhammadiyah Purwokerto, 2023)
This research aims to reveal the creativity of teacher pedagogy with creative and participatory learning in provoking the curiosity, activeness and enthusiasm of students. The application of pedagogical creativity as a search or an effective way to develop pedagogical creativity makes it possible to establish that innovative technologies have great potential in developing pedagogical creativity . Method The qualitative method was chosen to explore and give in-depth meaning to the data obtained and to be able to present more meaningful pedagogic creativity research results. Data analysis used descriptive analysis, starting with grouping the same data, then interpretation was carried out to give meaning to each sub-aspect and the relationship between one another. To carry out an analysis or interpretation of all aspects to understand the meaning of the relationship between one aspect and another which is the focus of further research is interpreted or interpreted. development of pedagogical creativity of teachers and students. The research findings show that many challenges to pedagogical creativity in pedagogical practice are manifested in the pattern of: 1) the effective application by a person of the experiences created in new conditions; 2) in repair known according to the new task; in the development of science and development; 3) in the ability to prove intuitive and pre-prepared decisions; 4) in the ability to dream, see near and distant prospects; 6) in the ability to develop ideas and see a series of options in their decisions; 7) to reveal the unknown regularity of previous training and education; 8) in the ability to conduct experiments, deeper research work. Thus, these findings can become the basis for further studies on improving and creating new approaches to the development of pedagogical creativity in the process of arts and culture craft education.